2009
DOI: 10.1007/s10519-009-9316-6
|View full text |Cite
|
Sign up to set email alerts
|

Wait For It! A Twin Study of Inhibitory Control in Early Childhood

Abstract: Inhibitory control (IC) is a dimension of child temperament that emerges in toddlerhood and involves the ability to regulate behavior in response to instructions or expectations. In general, children with low levels of IC have more cognitive and social difficulties, and higher levels of problem behaviors. Unfortunately, there is a paucity of research on the heritability of this important behavioral dimension. The present study used a twin design to examine the extent to which genetic and environmental factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 62 publications
6
60
0
Order By: Relevance
“…Specifically, high levels of inhibitory control were associated with high levels of reparation via the positive associations of caregiver-reported sympathy and guilt. The primacy of inhibitory control in this mediational chain is in line with recent twin studies documenting a significant genetic component of inhibitory control (Gagne & Saudino, 2010;Gagne et al, 2011). For example, Gagne and Saudino (2010) found that genetic factors accounted for 58% of the variance in caregiver-reported inhibitory control in a sample of 294, 24-month-old twin pairs.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Specifically, high levels of inhibitory control were associated with high levels of reparation via the positive associations of caregiver-reported sympathy and guilt. The primacy of inhibitory control in this mediational chain is in line with recent twin studies documenting a significant genetic component of inhibitory control (Gagne & Saudino, 2010;Gagne et al, 2011). For example, Gagne and Saudino (2010) found that genetic factors accounted for 58% of the variance in caregiver-reported inhibitory control in a sample of 294, 24-month-old twin pairs.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to its hypothesized role in promoting sympathy, inhibitory control may afford children with the regulatory capacity to curb overarousal (e.g., anger and frustration), reflect upon the wrongfulness of their transgression (e.g., feel guilty), and engage in reparation. The primacy of inhibitory control in this theoretical framework has been supported by recent twin studies establishing a significant genetic component of inhibitory control (Gagne & Saudino, 2010;Gagne, Saudino, & Asherson, 2011). Also in line with the present theorizing, recent research has considered the role of sympathy in mediating the effect of temperamental tendencies on prosocial behavior (see Edwards et al, 2014).…”
Section: Inhibitory Control Moral Emotions and Reparative Behaviorsupporting
confidence: 73%
See 2 more Smart Citations
“…It is clear from the literature that children who are already bilingual show a variety of cognitive advantages especially in the areas of inhibitory/executive control (Bialystok, 2009). However, the social skills of bilingual children have rarely been examined (Hakuta & Garcia, 1989;Han, 2010aHan, , 2010b, and the focus has been on cognitive advantages even though the construct of inhibitory control clearly relates to social and behavioral functioning as well (Gagne & Saudino, 2010). The present study tests the novel proposition that it may be that ELL children who are high to begin with in social skills, attachment with parent, behavioral control, and cognitive ability are those who are more likely to become bilingual over time, suggesting bidirectional relations between bilingualism and social and cognitive development.…”
Section: The Present Studymentioning
confidence: 99%